PENGEMBANGAN INSTRUMEN TES BERBASIS HIGHER ORDER THINKING SKILL (HOTS) PADA MATERI EKOLOGI KELAS X SEKOLAH MENENGAH ATAS - Restu Sitompul; Darmawati Darmawati; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: HOTS-based assessment is one of the demands of the 2013 curriculum. Students are expected to have high reasoning abilities by getting used to solving questions that are also HOTS in nature. However, the results of observations made in schools, HOTS questions are still rarely used by teachers in the process of assessing learning outcomes. This development research aims to produce a quality higher order thinking skill (HOTS) based test instrument. This research method is a research and development (R&D) method with the ADDIE model developed by Dick and Carry which consists of five stages, namely analyze, design, development, implement and evaluated. However, this research was carried out only until the development stage. Data was collected by means of interviews, validation and limited trials. The results of this study were 16 quality HOTS questions based on aspects of validation, reliability, level of difficulty, discriminating power and distracting function, namely 6 practice questions and 10 daily test questions. This is because only the 16 questions match the HOTS test criteria, namely 1) High validity with a total of 25 questions, namely material validity greater than 3.73, construction validity greater than 3.70 and language validity greater than 3. ,72. 2) High reliability, which is 0.73 for practice questions and 0.84 for daily test questions. 3) Has a moderate to difficult level of difficulty. 4) The discriminatory power of the questions is already good. 5) The distractors are all functioning properly.Key Words: Higher Order Thinking Skill, Tes Instrument.